„Czerwcowy sen o śniegu, śladzie, twarzy”. Wiersz Czesława Miłosza – - Antoniuk, Mateusz (Poznańskie Studia Polonistyczne. Seria Literacka, 2014)
<span style="font-family: 'Times New Roman','serif'; font-size: 12pt; mso-fareast-font-family: 'ＭＳ 明朝'; mso-ansi-language: EN-US; mso-fareast-theme-font: minor-fareast; mso-fareast-language: PL; mso-bidi-language: AR-SA;" lang="EN-US">The article is an attempt at a close reading of the poem 17 czerwca (“17 June”) by Czesław Miłosz. The author starts with a versological analysis, supposed to indicate in what way the poet achieved the tonal effects in the text. The interpretation that has been conducted makes visible a semantic unsolvability, which—according to the author—is born in the poem and, once discerned, cannot be easily neutralized.